Ὡς μήτηρ. Du caractère maternel d’Athéna - Vincent Cuche (Cahiers Mondes Anciens)
While being a parthenos, Athena is called a mother by the Athenians ; the Erichthonios myth is supposed to explain this paradox. Yet we know of many non-Athenian attestations of a mother-like Athena, which require a different kind of explanation. Beginning with two Iliadic passages where the goddess is compared to a mother, we find that throughout the poem, the Athena motherly figure is constructed in relation to other authentic mother goddesses, with whom she shares some kind of protective gestures, expressed with the same vocabulary. The presence of common semes between motherhood and military protection, facilited by the Greek analogical thinking, can still be seen in rites and cults of post-Homeric Greece, in which Athena becomes guardian and mother of the whole civic body as well as of each of its components. However, she supervises only a small part of Greek motherhood, which is due to the collective nature of the young Greek’s trophe.